1988
DOI: 10.1073/pnas.85.10.3513
|View full text |Cite
|
Sign up to set email alerts
|

Use of human peripheral blood lymphocytes to measure DNA binding capacity of chemical carcinogens.

Abstract: Although animal models have been used successfully to study metabolic activation and binding of carcinogens to DNA, only limited studies have been done in human systems. To circumvent the problems associated with the inaccessibility of human tissues and a lack of sensitive methods to detect DNA damage, we have investigated the capability of human peripheral blood lymphocytes in vitro to metabolize carcinogens to their DNA binding species by a 32P-labeled adduct assay. Freshly isolated lymphocytes were exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 9 publications
(10 reference statements)
3
22
0
Order By: Relevance
“…DNA was isolated from peripheral blood and its concentration was measured as described by (Gupta et al, 1988). Genotyping for all studied loci was performed by PCR-RFLP method.…”
Section: Genotypingmentioning
confidence: 99%
“…DNA was isolated from peripheral blood and its concentration was measured as described by (Gupta et al, 1988). Genotyping for all studied loci was performed by PCR-RFLP method.…”
Section: Genotypingmentioning
confidence: 99%
“…Therefore, DNA adducts have predominantly been studied in easily available peripheral white blood cells (WBC). Gupta et al (1988) demonstrated the capacity of human peripheral blood lymphocytes to in vitro metabolize a number of carcinogens, including B[α]P, to their DNA binding species and high inter-individual variations (up to 62 fold) in binding capacity of reactive PAH derivatives were observed. This variation in B[a]P related DNA adduct formation in vitro was found to be genetically controlled (Nowak et al, 1988) and may be indicative for individual differences in lung cancer susceptibility (Hawke et al, 1986;Nowak et al, 1992).…”
Section: Studies In Humansmentioning
confidence: 99%
“…lc, adduct4). Previous studies indicate that human lymphocytes can metabolize single chemicals as well as complex air pollution particle extracts (13,14). Future studies to evaluate the differences in labeling efficiency by comparing DNA adduct patterns in the nuclease P1 and butanol extraction versions of the postlabeling assay may reveal evidence for the presence ofadditional N-substituted arylamine adducts resulting from the nitroreduction ofnitrated PAH present in diesel extracts.…”
Section: In Vivo Treatmentsmentioning
confidence: 92%